PSIKOEDUKASI MINAT BACA DALAM MENINGKATKAN KEMAMPUAN KOGNITIF PADA ANAK DI SENTRA WIRAJAYA MAKASSAR DENGAN PENERAPAN MEDIA PUZZLE BERBASIS PENDEKATAN BEHAVIORISTIK - Akmal, Nur; Afif, Nur; Dilla, Andi Saputri; Samsalwa, Wa Ode Marwa (Devote: Jurnal Pengabdian Masyarakat Global, 2024)
Education is very important for children. One of the factors that children must have is cognitive ability in reading. This activity focuses on Children Against the Law (ABH) at Sentra Wirajaya Makassar, who have not and still lack reading skills totaling 3 people. This activity aims to provide psychoeducation and also improve children's reading skills using puzzle media. This activity was carried out in two steps, namely psychoeducation activities, and experiments using puzzle media as the treatment given to children. The experimental implementation method used was pre-experimental with a one-group pre-posttest design. Participants in this activity amounted to 5 children. Based on the results obtained from this activity, it shows that the application of puzzle media is proven to be able to improve cognitive abilities in terms of reading.